Analisis Imunoekspresi Programmed Death Ligand 1 (PD-L1) dan Indeks Proliferasi Ki-67 pada Tumor Astrositik Difus - Sri Suryanti; Billy Parulian Lubis; Hasrayanti Agustina; Hermin Aminah Usman; Bethy Surjawathy Hernowo; Ahmad Faried; Hendrikus Bolly (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2020)
BackgroundDiffuse astrocytic tumours (DAT) is a diffuse infiltrative astrocytoma tumor accompanied by molecular parameters in the form or absence ofIsocitrate Dehydrogenase (IDH) gene mutations. The DAT category without the examination of the IDH gene mutation is classified as NotOtherwise Specified (NOS). Ki-67 is a marker for DAT proliferation so that it can assess the degree of DAT. Diffuse astrocytic tumoursbehavior is influenced by proliferative ability and the presence of a tumor microenvironment. The tumor microenvironment PD-L1 factorinfluences DAT behavior and allows the development of target therapy in DAT cases. This study aimed to analyze the relationship betweenPD-L1 and Ki-67 imunoexpression in the histopathological degree of DAT.MethodsCross-sectional study of 30 paraffin blocks of DAT NOS cases from 2014-2018 in the Department of Anatomical Pathology RSUP dr. HasanSadikin, Bandung. The sample consisted of 15 cases of grade II, 7 cases of grade III and 8 cases of grade IV, carried outimmunohistochemical staining with GFAP, PD-L1 and Ki-67. Assessment of PD-L1 immunoexpression was carried out by the histoscoremethod. The Ki-67 assessment was assessed based on its distribution, which was <10% and ≥10%. PD-L1 and Ki-67 immunoexpressionwith histopathological degrees in DAT were statistically analyzed by Kolmogorof Smirnov test, however association betweenimmunoexpression of PD-L1 and Ki-67 were analyzed by chi-square test.ResultsThere was a significant relationship between PD-L1 immunoexpression and histopathological degree in DAT (p=0.005). There was asignificant relationship between Ki-67 immunoexpression and DAT histopathology degree and with PD-L1 (p=0.001 and p=0.010).ConclusionPD-L1 immunoexpression and proliferation rates affect the degree of DAT. Proliferation rate of DAT is influenced by PD-L1 so that in thisstudy, PD-L1 and Ki-67 can be used as a marker of prognosis predictors.